Webmasters guide to the wireless Internet - Powers, Shelley (Rockland, Mass. : Syngress Media ; London : International Thomson, 2001)
The wireless Web is a reality - don't get left behind! The wireless Web is not a future dream. It is here today. Already, more than 20 million people have access the Internet through PDAs, mobile phones, pagers and other wireless devices. What will people find on the Wireless Internet? This is the question that every Webmaster and Web developer is being challenged to answer. The Webmaster's Guide to the Wireless Internet provides the Wireless Webmaster with all of the tools necessary to build the next generation Internet. Packed with the essential information they need to design, develop, and secure robust, e-commerce enabled wireless Web sites. This book is written for advanced Webmasters who are experienced with conventional Web site design and are now faced with the challenge of creating sites that fit on the display of a Web enabled phone or PDA. The rapid expansion of wireless devices presents a huge challenge for Webmasters - this book addresses that need for reliable information There are lots of books for wireless developers - this is the first designed specifically for Webmasters Looks at security issues in a Wireless environment.
Keywords: Wireless communication systems; Internet; Web sites -- Design; Electronic books